Electricity consumption characteristics in Thailand residential sector and its saving potential - Kittikun Poolsawat; Watcharapong Tachajapong; Sukon Prasitwattanaseree; Wongkot Wongsapai (Energy Reports, 2020)
The actual state of electricity consumption characteristics in the residential sector in Thailand was presented. They were an essential information for the total energy usage estimation. They were used for investigating the feasibility of energy conservation. A questionnaire interview survey of 7,192 households for 41 kinds of appliances usage was conducted covering the whole part of Thailand in 2018. The characteristics of household electricity consumption was identified for both rural and urban areas. The whole country electricity consumption was estimated from the survey results extrapolation. The energy model, used in extrapolation, implies the majority of household electricity consumption in the area level. The result shows that overall electricity consumption in the household was 35,624.37 GWh in the year 2018. It comprised of air conditioner (26.50 %), refrigerator (19.33 %), light bulb indoor (14.93 %), rice cooker (6.82 %), television (6.10 %), fan (5.75 %), Electric bottle (3.35 %), light bulb outdoor (3.30 %), automatic pump (2.61 %), water heater (1.86 %), computer (1.67%), iron (1.55%), and other appliances (6.23 %). Around 13.97 % of electricity consumption, i.e. 4,975.89 GWh or 2.39 MtCO2, could be reduced by means of replacement with higher efficiency appliances.
Keywords: 330; Electricity consumption; Residential sector; Saving potential